Peran Strategis Manajemen Dalam Pengembangan dan Implementasi Pendidikan Islam: Pendekatan dan Tantangan - Muhammad Nur Jamaluddin Al Afghoni (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Islamic educational institutions are now experiencing increasingly complex and diverse developments, which require an organizational system that is structured effectively and efficiently. This complexity is especially evident in the need to manage the educational process with a more systematic managerial approach. Therefore, the application of management principles in the context of Islamic educational institutions is very important and attracts attention, both from practitioners in the field and experts in the field of education, who continue to explore ways to optimize educational management with the right management approach to date.